MORPHOCLINICAL ASPECTS OF CHRONIC HYPERTROPHIC RHINITIS (LITERATURE REVIEW) - Daniel Furculița (Arta Medica, 2023)
Objectives. Currently, chronic nasal obstruction due to hypertrophic rhinitis represents one of the most common problems in rhinology. Thus, it is important to mention that the etiology of the increase in size of the lower nasal turbinates can be varied and must be well specified, since the same aspect of the clinical picture can have a completely different substrate from a morphological point of view. In-depth knowledge of the changes in the structure of the turbinates are necessary and useful to form a correct diagnostic and therapeutic approach. The purpose of the given study was to perform a detailed analysis of the contemporary data of the specialized literature in order to determine the morphological conformation of the nasal mucosa in chronic hypertrophic rhinitis.